Faire obstacle à la vérité et tromper les attentes : Hitchcock et Wilder comme on les connaît peu - Julie Michot (Revue LISA)
Hitchcock’s and Wilder’s aesthetics and preferred themes seem so different that the two European-born directors have rarely been compared, although they were at the height of their fame at about the same period in Hollywood. And yet, they have much more in common than what might appear at first sight. Their detective films, in particular, are never pure entertainment, and they always imply a significant share of social critique, as is the case with The Paradine Case by Hitchcock (1947) and Witness for the Prosecution by Wilder (1957). Both movies appear to highlight the flaws in the English judicial system—since the action takes place in London—while in fact it is clear that the filmmakers’ judgment is much wider and also applies to their adopted country, the USA. This article intends to study the numerous similarities in style and content between these two unusual films—Hitchcock deciding to mix suspense and surprise; Wilder experimenting Hitchcock’s methods—, and it also seeks to analyze the various strategies developed by the directors to manipulate their public brilliantly.